Konsep Aritmetika pada Perubahan Kata Bahasa Arab - Nurul Hidayah; Mukmin Mukmin; Listia Eltika (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2023)
This study aims to find out the changes in Arabic words in terms of arithmetic perspectives that occur either changing in word classification or only changing in terms of users (fa'il) of the verb. This research uses library research, the focus of the study is 29 wazan contained in the morphology of the Arabic language. So, the analysis is an elaboration of the arithmetic patterns contained in the wazan. The results of this study show that the derivation (tashrif ishtilahy) consists of additional letters that are at the beginning, in the middle and at the end of the word, the addition of letters is varied in number, some get an additional one letter, some get an additional two letters, and the addition of three letters, this addition makes a fairly significant change in meaning, although the meaning still has the same root. In the letter subtraction only three letters are reduced (illat letters). Meanwhile, in the multiplication process, there is one letter that is duplicated in the form of tasydid after previously the word was added to a certain number of letters. In the inflection process, the letter added is a letter that indicates the number of performers of the verb and the gender of the perpetrator, while in nouns the change is found in the plural of estimates where the change is influenced by a certain wazan.